(untitled) (Research, Society and Development, 2019)
This article aims to identify which digital competences are required in contemporary society, within the perspective of their use in education. It can be said that in today’s society, which is supported by information, knowledge and learning, in a scenario of constant and complex changes driven by the advancement of technology, it is important that there are individuals prepared to be part of this process. For Rocha, Jucá e Silva (2019), a continuous effort of human innovations to transmit ideas and creations over time and space is noted. For this article a qualitative research was carried out, which, according to Minayo (2007) allows the researcher an in-depth analysis of the studied object. Initially, exploratory research was used in the search for theoretical bases through a literature review. We can conclude, from the above, it refers to the potential benefits of ICT for teaching-learning, including gains in achievement and motivation of students. It also adds the possibility of accessing content that is not offered in person, which is more convenient to access online. The second argument recognizes the omnipresence of technologies, which leads to the subsequent need to acquire the digital competence to be functional in society, since several services are available in the digital mode. As a consequence, the third argument emphasizes the need to invest in enhancing digital skills for social growth and economic competitiveness.